Effects of Rehabilitation Program on Quality of Life, Sleep, Rest-Activity Rhythms, Anxiety, and Depression of Patients With Esophageal Cancer: A Pilot Randomized Controlled Trial. Issue 2 (March 2022) - Chen, Hui-Mei; Lin, Yi-Yun; Wu, Yu-Chung; Huang, Chien-Sheng; Hsu, Po-Kuei; Chien, Ling-I; Lin, Yu-Jung; Huang, Hsiu-Li
Abstract : Background: Esophageal cancer patients experience severe symptoms and poor quality of life. Objective: We examined the effects of a rehabilitation program on quality of life, sleep, rest-activity rhythms, anxiety, and depression of esophageal cancer patients. Methods: Forty-four patients with esophageal cancer were randomly assigned to an experimental group, which underwent a 12-week brisk walking and diet education program, or a control group, which received standard care. Health-related quality of life, subjective and objective sleep quality, rest-activity rhythms, anxiety, and depression were assessed at baseline and post intervention. Results: A generalized estimating equation analysis revealed that, after intervention, compared with the control group, the experimental group exhibited significantly improved reflux ( P = .022; effect size, 0.32) and marginally improved emotional ( P = .069; effect size, 0.27) and social ( P = .069; effect size, 0.27) functions; constipation ( P = .050; effect size, 0.29), eating difficulty ( P = .058; effect size, 0.27), anxiety ( P = .050; effect size, 0.29), and total sleep time ( P = .068; effect size, 0.39). Conclusions: The rehabilitation program may improve health-related quality of life and sleep and alleviate anxiety in patients with esophageal cancer. Implications for Practice: A rehabilitation program comprising exercise and diet education is a feasible and low-cost intervention for improving quality of life of patients with esophageal cancer. Healthcare team members may consider it as a nonpharmacological treatment option for patients.